Analisis Sebaran BOD dan TSS pada Sungai Kapuas di Sekitar PTPN XIII Rimba Belian Kabupaten Sanggau - Larasati, Allisha; Winardi, Winardi; Purnaini, Rizki (Universitas Trunojoyo Madura, 2024)
The research area, namely the Kapuas River, serves as a disposal site for waste from household activities, including bathing, washing, and sanitation (MCK), as well as waste from the industrial and plantation sectors. PTPN XIII Rimba Belian, located in Rimba Belian Hamlet, Semerangkai Village, Kapuas Subdistrict, Sanggau Regency, operates in palm oil (CPO) production, resulting in the formation of waste containing organic compounds such as BOD and TSS. Waste from the PTPN factory's wastewater treatment plant (IPAL) that enters the river can render the river unsuitable for use, leading to diseases, and may cause a decrease in the river's assimilative capacity. Therefore, modeling is needed to analyze the spread of BOD and TSS and calculate the assimilative capacity for pollution using the WASP 7.5 model. The objective of this modeling is to predict the river's assimilative capacity for pollution and the impact of changes in water quality caused by oil palm plantations around the Kapuas River in the research location. The modeling is conducted by segmenting the river into 6 segments. The results of this study indicate that the PTPN XIII factory plays a significant role in contributing to BOD and TSS parameters. The assimilative capacity for BOD in the research location shows positive values in all segments except for segment 4, which has a negative value. Meanwhile, the assimilative capacity for TSS pollution load shows positive values in all segments.